Pengelolaan Sport Tourism Sebagai Daya Tarik Wisata Di Tapanuli Utara (Studi Komparasi Paralayang Huta Ginjang Dengan Arung Jeram Aek Situmandi) - Sanovida Tamba; Mery Silalahi; Tio R.J Nadeak; Elvri Teresia Simbolon (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze and compare the management of sports tourism in North Tapanuli Regency, namely Huta Ginjang Paragliding and Aek Situmandi Rafting. This study uses a descriptive qualitative method with a comparative study approach, so that each aspect of management is analyzed to find similarities, differences, and management advantages. Data was obtained through observations, interviews with the Tourism Office, FAJI, tourism managers, tourists, and documentation, then analyzed using management theory that includes development, institutional, and regulation. The results of the study show that in terms of development, both destinations have short-term plans in the form of annual events and long-term plans to strengthen tourist attractions. Paragliding Huta Ginjang emphasizes international events and strengthening pilot licenses, while Aek Situmandi Rafting highlights community-based development. In the institutional aspect, both involve sports associations, the government, and the community. However, the Huta Ginjang Paragliding institution is more formal and structured, while the Aek Situmandi Rafting institution is more collaborative with the community as the main actor. In terms of regulation, both destinations emphasize safety standards, licenses, and formal licensing mechanisms. The difference is that paragliding focuses on the regulation of weather and flight factors, while rafting focuses on river conditions and rafting techniques. Comparatively, Aek Situmandi Rafting has great potential, but its management still faces limited facilities, especially the availability of rafting equipment. On the other hand, the Huta Ginjang Paragliding is considered to have better management because it is supported by adequate equipment, international safety standards, national-international scale events, and more professional institutional coordination. Thus, this study confirms that Huta Ginjang Paragliding is currently superior in managing sports tourism compared to Aek Situmandi Rafting